Fracture Resistance of Endodontically Treated Upper Premolar Teeth Restored with Bulk-fill and Conventional Resin Composite# - Gök, Adem; Dallı, Mehmet; Dülgergil, Çoruh Türksel (Cumhuriyet University Faculty of Dentistry, 2022)
Objectives: The aim of this in vitro study was to evaluate the fracture resistance of endodontically treated upper premolar teeth restored with different resin composites. Materials and Methods: Hundred and eight maxillary premolar teeth were randomly divided into nine groups (n=12). The teeth in the first group were left intact and tested as unprepared group 1 (negative control). Other eight groups were prepared with MOD cavities and endodontically treated. The teeth in group 2 (positive control) were unrestored. Other groups were restored with different resin composites. Group 3: conventional resin composite and group 4-9 six bulk fill resin composite (group 4: 3M Filtek Flowable Bulk Fill, group 5: 3M Filtek Posterior Bulk-fill, group 6: Voco X-tra base, group 7: Voco X-tra fil, group 8: Dentsply SDR Flow, group 9: Dentsply Quixfil). Single Bond Universal was applied as self-etch, according to application instructions. The restored teeth were stored in distilled water for 24 hours at 37°C. The compressive force was applied parallel to the long axis of the teeth. The test was carried out at a speed of 1mm/min. ANOVA and Tukey HSD tests were used in the analysis of the data. Results: Negative control group showed significantly higher fracture resistance than other tested groups. The bulk-fill resin composites were showed higher fracture resistance than teeth restored with conventional resin composite. No statistically significant differences were found in the fracture resistance values of the bulk-fill resin composites. The significantly lowest values were obtained in the positive control group (group II) Conclusions: The fracture resistance values of endodontically treated teeth restored with bulk-fill composites were higher than teeth restored with conventional resin composite. © 2022. All Rights Reserved.
Bulk-Fill ve Geleneksel Kompozit Rezin ile Restore Edilmiş Endodontik Tedavi Görmüş Üst Premolar Dişlerin Kırılma Direncinin Değerlendirilmesi#
Keywords: Bulk-Fill Composite; Bulk-Fill Kompozit; Endodonti Kompozit Rezin; Endodontic Treatment; Endodontics; Endodontik Tedavi; Fracture Resistance; Kırılma Direnci; Resin Composite